Kuhn-Tucker Theorem for Infinite Dimension - Ferreira, M. A. M. (EasyChair Preprint no. 13843, 2025)
This work objective is the presentation of Kuhn-Tucker theorem with the consideration of infinite dimension. So, the mathematical fundaments of this result, not so important in Mathematical Programming but a very challenging problem from the mathematical point of view, are shown in a very simple way. We will see how this result can be obtained in the context of real Hilbert spaces through the separation theorems.